2005
DOI: 10.1038/sj.cdd.4401762
|View full text |Cite
|
Sign up to set email alerts
|

CED-4 forms a 2 : 2 heterotetrameric complex with CED-9 until specifically displaced by EGL-1 or CED-13

Abstract: The pathway to cell death in Caenorhabditis elegans is well established. In cells undergoing apoptosis, the Bcl-2 homology domain 3 (BH3)-only protein EGL-1 binds to CED-9 at the mitochondrial membrane to cause the release of CED-4, which oligomerises and facilitates the activation of the caspase CED-3. However, despite many studies, the biophysical features of the CED-4/CED-9 complex have not been fully characterised. Here, we report the purification of a soluble and stable 2 : 2 heterotetrameric complex form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
29
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 39 publications
(73 reference statements)
3
29
2
Order By: Relevance
“…Both mutant peptides were able to dissociate the complex as with wild-type EGL-1BH3, but as previously, no dissociation was observed with the BimBH3 peptide. 22 These results demonstrate the exquisite sensitivity of prosurvival protein:BH3 domain interactions and suggest BH3 domain-binding profiles can be readily manipulated.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Both mutant peptides were able to dissociate the complex as with wild-type EGL-1BH3, but as previously, no dissociation was observed with the BimBH3 peptide. 22 These results demonstrate the exquisite sensitivity of prosurvival protein:BH3 domain interactions and suggest BH3 domain-binding profiles can be readily manipulated.…”
mentioning
confidence: 85%
“…21 We have also shown that mammalian BH3-only proteins such as Bim and Bad, unlike EGL-1, cannot dissociate CED-4:CED-9 complexes. 22 This suggests that either these mammalian BH3-only proteins cannot engage CED-9 directly, or alternatively, they bind CED-9 but cannot induce the conformational change necessary for CED-4 release. 11 These studies indicate that the molecular mechanisms, and evolutionary conservation, of nematode and mammalian apoptosis pathways are still not completely understood.…”
mentioning
confidence: 99%
See 3 more Smart Citations